Individual's career strategies and person-environment fit as the prerequisites to attain career success - Loo, Xing Li (Universiti Malaysia Sarawak (UNIMAS), 2011)
This study investigates the relationship between perception of individual's career strategies and person-environment fit as the prerequisites to attain career success. Survey questionnaire method was used to collect data from samples from government sector employees. Respondents were asked to respond to 50 questions in relation with their method to attain career success. Pilot study was carried out onto 35 respondents in order to test the reliability of the questionnaire before conducting the actual study. The data gathered from the pilot and actual study was analyzed using SPSS version 17.0. The direct relationship between career strategies and person-environment fit with career success were determined by using Spearman's Rank Order Correlation Analysis. The most dominant factors were determined by using Multiple Regression analysis. The analysis shows that five of the alternate hypotheses are accepted. Overall, the findings indicate that person-environment fit is proven that affect the employee's career success in the organization. Hence, it is important for organization to acknowledge the career strategies efforts and person-environment fit in the organization in order to ensure an excellent and productive performance by their employees. Therefore, this study supports the empirical study which studied by the previous researchers.